Application of electro-Fenton and photoelectro-Fenton processes for the degradation of contaminants in landfill leachate - Crispim, Alana C.; Araújo, Danyelle M. de; Martínez-Huitle, Carlos A. [UNESP]; Souza, Fernanda L.; Santos, Elisama V. dos [UNESP] (My University, 2022)
Worldwide, most solid waste ends its life in landfill sites, which have a significant environmental impact in several respects. In particular, rainfall over landfill sites results in the production of an aqueous leachate containing compounds having low biodegradability, high toxicity, and a high organic load. For this reason, this study aims to investigate the applicability of electro-Fenton (EF) and photoelectro-Fenton (PEF) processes as alternative for treating a local landfill effluent with high organic content (chemical oxygen demand (COD) = 2684.7 mg-O2 L −1) in a continuous-flow reactor (using, for first time, this kind of system with higher electrodes area of 35 cm2) using boron-doped diamond anode (Nb/BDD) and a carbon felt cathode (FC) electrodes. The effects of current density j (30, 60 and 90 mA cm−2) and UV radiation wavelength (UVA and UVC) were studied to evaluate the treatment efficiency as well as the energy consumption. Results clearly showed that, the best efficiencies removing organic matter, in terms of COD, were about 66%, 68% and 89% with an energy consumption of only 19.41, 17.61 and 17.59 kWh kg COD−1 for EF, PEF-UVA and PEF-UVC respectively, at 90 mA cm−2 after 4 h of operation. The treatment of this kind of effluent produced organic and inorganic by-products, the acetic and formic acids as well as NO2−, NO3−, and NH4+, being assessed their concentrations.
Keywords: Electro-Fenton; Electrochemical technologies; Landfill leachate; Photoelectron-Fenton